Eco-Qur’anic Pesantren and Environmental Stewardship: Evidence from Baitul Hikmah Tempurejo Jember - Sofiah; Zulfa Ahmad Kurniawan; Muhammad Korib Hamdani (EKONOMIKA SYARIAH : Journal of Economic Studies, 2026)
The environmental crisis is a global issue that threatens human sustainability and necessitates new concepts to address it. Eco-Qur’anic Pesantren is a concept designed to instill environmental awareness rooted in Quranic values. This study aims to analyze the implementation of Quranic values in shaping eco-friendly character at Pesantren Baitul Hikmah Tempurejo, Jember, and its contribution to the Sustainable Development Goals (SDGs). This research employs a qualitative case study approach to explore environmental education practices within the pesantren context. Data collection involves participatory observation, in-depth interviews, and documentation, with data validity ensuring credibility, transferability, dependability, and confirmability. The results indicate that the implementation of Quranic values is realized through curriculum integration, green land utilization programs, 3R-based (Reduce, Reuse, Recycle) waste management, and the Kyai's exemplary leadership. This study concludes that the Eco-Qur’anic concept contributes to achieving SDGs, specifically Quality Education (SDG 4), Sustainable Cities and Communities (SDG 11), Responsible Consumption and Production (SDG 12), Climate Action (SDG 13), and Partnerships for the Goals (SDG 17).